2009
DOI: 10.1111/j.1365-3083.2009.02310.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salivary Gland Homogenate from Wild‐Caught and Laboratory‐Reared Lutzomyia longipalpis on the Evolution and Immunomodulation of Leishmania (Leishmania) amazonensis Infection

Abstract: We investigated the effects of Lutzomyia longipalpis salivary glands homogenate of wild‐caught and laboratory‐reared vectors on the lesion evolution and immunomodulation of the infection caused by Leishmania (Leishmania) amazonensis. To compare the effect of both salivary glands homogenate (SGH), C57BL/6 mice were inoculated subcutaneously into the hind footpads or into the ear dermis with 106 promastigotes in the presence or not of SGH from wild‐caught and laboratory‐colonized sand flies. Comparing SGH groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
0
16
1
2
Order By: Relevance
“…5 It was reported that colonized and wild-caught Lutzomyia longipalpis differ in the composition and the amount of salivary proteins and these differences may account for the lower effect observed on the modulation of experimental Leishmania infection by wild-caught SGH. 6,7 Thus, these studies provide good evidence that the outcome of Leishmania infection differs significantly between colonized and wild-caught salivary gland proteins. Our aim in this study was to assess the protective effect of pre-immunization with SGH of long-term colonized P. papatasi on experimental L. major challenge co-inoculated with SGH of wild-caught P. papatasi .…”
mentioning
confidence: 74%
“…5 It was reported that colonized and wild-caught Lutzomyia longipalpis differ in the composition and the amount of salivary proteins and these differences may account for the lower effect observed on the modulation of experimental Leishmania infection by wild-caught SGH. 6,7 Thus, these studies provide good evidence that the outcome of Leishmania infection differs significantly between colonized and wild-caught salivary gland proteins. Our aim in this study was to assess the protective effect of pre-immunization with SGH of long-term colonized P. papatasi on experimental L. major challenge co-inoculated with SGH of wild-caught P. papatasi .…”
mentioning
confidence: 74%
“…Therefore, these experiments may need to be repeated normalizing the amount of salivary proteins when using colonized vs. wild caught flies. In fact, Laurenti et al (2009a,b) showed that salivary proteins from field-captured L. longipalpis impacted the immune system differently from laboratory-reared sand flies. Nevertheless, this work clearly indicates (by SDS-PAGE analysis) that one salivary gland pair from wild caught sand flies had fewer amounts of proteins when compared to a salivary gland pair from colonized flies.…”
Section: Challenges For Vaccine Developmentmentioning
confidence: 99%
“…Among these factors, the infection-potentiating effect of sand fly salivary molecules [17], [18], [19], [20] has generated a great deal of excitement in the research community because: 1) it provides clues about immunobiological determinants of resistance or susceptibility to Leishmania infection and 2) it provides additional targets for vaccines to prevent leishmaniasis. Sand fly saliva plays an important role in the transmission of Leishmania parasites, facilitating their survival and dissemination in tissues of the vertebrate hosts by promoting a Th2-skewed immune response at the bite site [21], [22], [23]. Vaccines directed to sand fly saliva are expected to induce protective immunity by neutralizing the biological activity of salivary immuno-modulators and by generating a tissue microenvironment that promotes the destruction of parasites delivered, along with saliva, while sand flies take a blood meal [17], [24], [25].…”
Section: Introductionmentioning
confidence: 99%